1999
DOI: 10.1046/j.1365-2443.1999.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interaction of Seven in absentia homolog‐1A and Ca2+/calmodulin with the cytoplasmic tail of group 1 metabotropic glutamate receptors

Abstract: Background: Group 1 metabotropic glutamate receptors (mGluR1 and mGluR5) are coupled to inositol trisphosphate/Ca 2þ signaling via G proteins and play an important role in excitatory synaptic transmission. To explore the regulation of group 1 mGluR function, we applied the yeast two-hybrid system using the intracellular carboxy-terminal domain of group 1 mGluRs (group 1 ct-mGluRs) and attempted to identify novel protein-protein interactions of group 1 mGluRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 35 publications
3
74
0
Order By: Relevance
“…To map interacting domains within the binding partners, we analyzed the interaction between PP1␥1 and mGluR C termini in yeast cells by the ability of transformants to grow on selective media upon activation of His3 and LacZ reporter genes. The complete C termini of mGluR1a, mGluR5a, and mGluR5b showed transactivation of the reporter genes, which had been also noticed by other groups (21,25). Therefore, we used C-terminally truncated constructs for our studies (see stars in Fig.…”
Section: Pp1␥1mentioning
confidence: 66%
“…To map interacting domains within the binding partners, we analyzed the interaction between PP1␥1 and mGluR C termini in yeast cells by the ability of transformants to grow on selective media upon activation of His3 and LacZ reporter genes. The complete C termini of mGluR1a, mGluR5a, and mGluR5b showed transactivation of the reporter genes, which had been also noticed by other groups (21,25). Therefore, we used C-terminally truncated constructs for our studies (see stars in Fig.…”
Section: Pp1␥1mentioning
confidence: 66%
“…CaM binding to receptors often competes with other protein-protein interactions, and CaM competition with spectrin, and ␣-actinin binding to NMDA receptors is one such example (17,24,33,34). Similarly, it has also been shown that CaM binding to mGluR5 inhibits the binding of the E3 ligase Siah-1A in vitro (13). Recently Siah-1A has been shown to promote monoubiquitination of ␣-synuclein, leading to its aggregation (35).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the binding sites for these protein-protein interactions reside within the long intracellular C-terminal domain of mGluR5, suggesting that this region is critical in the functional regulation of mGluR5. For example, the Homer proteins bind to the PPxxFR motif within the distal C terminus, the Tamalin protein associates with the distal C terminus, and calmodulin (CaM) and the E3 ligase Siah-1A bind to the first one-third of the mGluR5 C terminus (12)(13)(14)(15). However, the dynamic regulation of these protein-protein interactions has not been described.…”
mentioning
confidence: 99%
“…In many cases the negative signaling is due to a caspase-mediated cleavage of the receptor C-terminal domain (CTD) which either releases a pro-apoptotic C-terminal receptor fragment (Bordeaux et al, 2000;Llambi et al, 2001), or exposes a pro-apoptotic region that presumably remains bound to the cell membrane (Mehlen et al, 1998;Forcet et al, 2001;Thibert et al, 2003). While a specific cleavage of the mGlu1 CDT has not been described, it should be pointed out that a sequence analysis of the long CTD of the mGlu1a splice variant reveals six putative caspase cleavage sites, as well as multiple sequences that may potentially interact with a variety of intracellular proteins including: seven in absentia homolog-1A (Siah-1A) and calmodulin (Ishikawa et al, 1999;Kammermeier and Ikeda, 2001), G-proteincoupled receptor kinases (Dale et al, 2000), alpha-tubulin (Ciruela et al, 1999), tamalin/ cytohesin complex (Kitano et al, 2002), homer proteins (Brakeman et al, 1997;Tu et al, 1999), protein phosphatase 1C (Croci et al, 2003), protein kinase C, regulators of G-protein signaling (RGS) proteins, Src-family protein tyrosine kinase and arrestins (Valenti et al, 2002;Hermans and Challiss, 2001). Therefore, the mGlu1 CTD is well equipped to participate and interfere in various intracellular signaling processes.…”
Section: Discussionmentioning
confidence: 99%